The city at night: activating Washington Square Park through nighttime programming - Butler, Alyssa Ailts (Kansas State University, 2014)
Many cities are beginning to embrace the 24-hour city concept, where people stay up later, businesses are open 24 hours a day, and nighttime economies are expanding (Bianchini, 1995). Cities can reap social, economic, and cultural benefits by extending business hours into the night, creating safe and attractive reasons for people to utilize urban public spaces during these times, and connecting these spaces both physically and culturally to surrounding districts (Roberts, 2009). Washington Square Park in Kansas City, Missouri is an underused civic space identified as a potential anchor park for the city that could become a downtown destination, both day and night (KCDC, 2012). This report focuses on the nighttime aspects of the park, making it a vibrant evening destination for downtown Kansas City that could help boost economic activity, create new social opportunities and strengthen physical, and cultural connections to surrounding districts. Through a process of project goal finding, questioning and analysis, a set of programming strategies was developed and applied to a design for Washington Square Park that reflects the needs of stakeholders, relevant theory, and lessons learned from built precedents. Key components of a successful nighttime programming strategy for Washington Square Park include: extending business hours into the night; increasing the amount of retail, restaurant and building uses; establishing a sense of place with lighting; enhancing views; creating strong connections to surrounding areas; creating attractive amenities that extend into the night; and creating a space that is welcoming and safe with appropriate levels of lighting, activity and security. Through this research I have found that nighttime programming for an urban civic park can be an effective way of helping to create an active downtown destination for cities, benefiting the area socially, economically and culturally. Utilizing evening programming strategies in Washington Square Park can, not only help to activate the space during more hours of the day, but also create a unique sense of place that defines the park as an urban destination both day and night. By including nighttime programming strategies into design considerations, new opportunities for economic growth and social interaction can be revealed.
Keywords: Nighttime Programming; Urban civic parks; Urban design; Lighting design; Landscape Architecture (0390)